YMCA Indian Guides Kite Flying at Woodward Park - Watkins, Howard::::::::: (1988)
Members of Sierra Nation's Apache Tribe: Front: Adam Watkins, ?, Jared Gordon, Dean Gordon, Josiah Gordon, Chuck Sheehan, Charlie Sheehan, Dennis Metzler, and David Metzler; Standing: David Holmes, Bryce Holmes, and Howard Watkins